Weapons of War in the Future: An Analysis of M.A.K. Halliday's Semiotics on the Aljazeera.net Media Portal - Nurul Luthfiyyah; Muassomah (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the construction of meaning in the discourse of Al Jazeera news entitled